Financial Controlling as a System of Efficient Management of Joint Activities of Enterprises (Economics and region, 2020)
The theoretical approaches to the definition of the essence of concepts "controlling" and "financial control" are generalized and analyzed. As a result, it is discovered that scientists consider financial control as a subsystem controlling an enterprise or as an enterprise management system as a whole. It is proposed the self-determination of financial control of joint activities. It is substantiated that financial control is a system of effective management of financial and economic activity of a joint venture, which includes planning, accounting, control, analysis, management information provision for achievement of strategic and operational objectives of joint venture. The strategic focus of financial control is emphasized.
Keywords: controlling; financial control; planning; control; management; joint venture; joint activity